Manifestations of Satire in the Writings of Abbas Dakhl Hassan - Hussein, Asst.L. Ikhlas Hassan Hussein (Sulaimani Journal for Humanities, 2025)
The story teller and journalist( Abbas Dakhel Hassan) is one of the writers anthe art of mockery in Iraq,which was his special character in writing ,even on the most seriour topics, politically, religionsly or socially. As he states that mockery is the weaponfor the defenseless, exactly as writing is a weapon against injustice and spreading awareness. The research found that Abbas writings are dominate by mockery in most his cultural, social and political writings and also mockery in Abbas writing is not atype of redemption but the mockery of the reformer, critic and preacher that shows the defects in his society and ruling authority to get rid of them in a mockery manner. We chose this literary art within the writings of Abbas Dakhel Hassan for subjective motives, represented by the pleasure of researching this topic, objective motives, represented by the pleasure of researching this topic, and other objective motives, represented by shedding light and searching for connotations of sarcasm scattered in Abbas Dakhel Hassan’s writings, and discovering its deep dimensions. In our research (Manifestations of sarcasm in the writings of Abbas Dakhel Hasan), we reviewed: sarcasm language and terminology, types of sarcasm, and finally methods of sarcasm. Then we concluded the research with the most important results after this study, followed by a list of sources and references.